2006
DOI: 10.1017/s0265021506000056
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring sedation in critically ill patients

Abstract: Sedation should be monitored routinely in intensive care units. The Ramsay and the Observer's Assessment of Alertness and Sedation scales showed equal efficacy. Bispectral index might prove useful for discriminating between deeper levels of sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Sedation requirements obviously differ among patients; nevertheless, the variation in recommended ranges in included studies indicates some uncertainty in what constitutes optimal sedation. Of the studies using the Ramsay scale, recommended ranges were 2 to 3 (recommended in two studies [21,22]), 2 to 4 (two studies [23,24]), 2 to 5 (two studies [25,26]), 3 to 4 (two studies [27,28]) and 4 to 5 (one study [29]), while three studies did not recommend specific levels but recommended that levels be optimised for each individual patient [30-32]. This variation was reflected in the other scales used; for studies recommending a modified Ramsay scale, recommended ranges were 1 to 4 [33], 3 to 4 [34], 4 [35], and 5 to 6 (the last range being specifically for seriously injured patients [36]) or targets optimised for each patient [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Sedation requirements obviously differ among patients; nevertheless, the variation in recommended ranges in included studies indicates some uncertainty in what constitutes optimal sedation. Of the studies using the Ramsay scale, recommended ranges were 2 to 3 (recommended in two studies [21,22]), 2 to 4 (two studies [23,24]), 2 to 5 (two studies [25,26]), 3 to 4 (two studies [27,28]) and 4 to 5 (one study [29]), while three studies did not recommend specific levels but recommended that levels be optimised for each individual patient [30-32]. This variation was reflected in the other scales used; for studies recommending a modified Ramsay scale, recommended ranges were 1 to 4 [33], 3 to 4 [34], 4 [35], and 5 to 6 (the last range being specifically for seriously injured patients [36]) or targets optimised for each patient [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…OAA/S is a validated clinical measure of sedation level. 15,16 In using the OAA/S assessment, we also hope to generalize our results to settings where bispectral index monitor is unavailable in the operating room.…”
Section: Discussionmentioning
confidence: 81%
“…15 More importantly, previous studies have shown that OAA/S score is better indicator of the level of sedation than electroencephalography. 15,16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations